Book Review of "Generalized Anxiety Disorder" - Kesling, Gary (Canadian Journal of Counselling and Psychotherapy, 2012)
The text is part of the series in the Advances in Psychotherapy – Evidence-Based Practice (Volume 24: Generalized Anxiety Disorder). The book is written to provide a practical and reader-friendly guide for a functional approach to generalized anxiety disorders. The book reads as a primer for clinicians, beginning professionals, and students looking for a practical and well-organized approach to working with individuals who may be experiencing a range of anxiousness-producing problems. The text includes theories and models, diagnostic and treatment indications, a case vignette, and some specific assessment tools for differentiating various anxiety disorders.